Tualang honey improves memory performance and decreases depressive-like behavior in rats exposed to loud noise stress - Azman, Khairunnuur Fairuz; Zakaria, Rahimah; Aziz, Che Badariah Abd; Othman, Zahiruddin; Al-Rahbi, Badriya (Medknow Publications, 2015)
Recent evidence has exhibited dietary influence on the manifestation of different types of behavior induced by stressor tasks.The present study examined the effects of Tualang honey supplement administered with the goal of preventing or attenuating the occurrence of stress-related behaviors in male rats subjected to noise stress. Forty-eight adult male rats were randomly divided into the following four groups: i) nonstressed with vehicle, ii) nonstressed with Tualang honey, iii) stressed with vehicle, and iv) stressed with honey. The supplement was given once daily via oral gavage at 0.2 g/kg body weight. Two types of behavioral tests were performed, namely, the novel object recognition test to evaluate working memory and the forced swimming test to evaluate depressive-like behavior. Data were analyzed by a two-way analysis of variance (ANOVA) using IBM SPSS 18.0. It was observed that the rats subjected to noise stress expressed higher levels of depressive-like behavior and lower memory functions compared to the unexposed control rats. In addition, our results indicated that the supplementation regimen successfully counteracted the effects of noise stress. The forced swimming test indicated that climbing and swimming times were significantly increased and immobility times significantly decreased in honey-supplemented rats, thereby demonstrating an antidepressant-like effect. Furthermore, cognitive function was shown to be intensely affected by noise stress, but the effects were counteracted by the honey supplement. These findings suggest that subchronic exposure to noise stress induces depressive-like behavior and reduces cognitive functions, and that these effects can be attenuated by Tualang honey supplementation. This warrants further studies to examine the role of Tulang honey in mediating such effects.